How Vulnerable Are Arab Countries to Global Food Price Shocks? - Ianchovichina, Elena (World Bank, Washington, DC, 2012)
This paper presents new estimates of pass-through coefficients from international to domestic food prices by country in the Middle East and North Africa. The estimates indicate that, despite the use of food price subsidies and other government interventions, a rise in global food prices is transmitted to a significant degree into domestic food prices in many countries in the Middle East and North Africa, although cross-country variation is significant. In nearly all countries, domestic food prices are highly downwardly rigid. The finding of asymmetric price transmission suggests that not only international food price levels matter, but also food price volatility. High food pass-through tends to increase inflation pressures, where food consumption shares are high. Domestic factors, often linked to storage, logistics, and procurement, have also played a major role in explaining high food inflation in the majority of countries in the region.